Therapeutic endoscopic ultrasound: European Society of Gastrointestinal Endoscopy (ESGE) Technical Review - van Wanrooij, Roy L. J.; Bronswijk, Michiel; Kunda, Rastislav; Everett, Simon M.; Lakhtakia, Sundeep; Rimbas, Mihai; Hucl, Tomas; Badaoui, Abdenor; Law, Ryan; Arcidiacono, Paolo Giorgio; Larghi, Alberto; Giovannini, Marc; Khashab, Mouen A.; Binmoeller, Kenneth F.; Barthet, Marc; Pérez-Miranda, Manuel; van Hooft, Jeanin E.; van der Merwe, Schalk W. (Endoscopy, 2022)
1 ESGE recommends a prolonged course of a prophylactic broad-spectrum antibiotic in patients with ascites who are undergoing therapeutic endoscopic ultrasound (EUS) procedures.Strong recommendation, low quality evidence.2 ESGE recommends placement of partially or fully covered self-expandable metal stents during EUS-guided hepaticogastrostomy for biliary drainage in malignant disease.Strong recommendation, moderate quality evidence.3 ESGE recommends EUS-guided pancreatic duct (PD) drainage should only be performed in high volume expert centers, owing to the complexity of this technique and the high risk of adverse events.Strong recommendation, low quality evidence.4 ESGE recommends a stepwise approach to EUS-guided PD drainage in patients with favorable anatomy, starting with rendezvous-assisted endoscopic retrograde pancreatography (RV-ERP), followed by antegrade or transmural drainage only when RV-ERP fails or is not feasible.Strong recommendation, low quality evidence.5 ESGE suggests performing transduodenal EUS-guided gallbladder drainage with a lumen-apposing metal stent (LAMS), rather than using the transgastric route, as this may reduce the risk of stent dysfunction.Weak recommendation, low quality evidence.6 ESGE recommends using saline instillation for small-bowel distension during EUS-guided gastroenterostomy.Strong recommendation, low quality evidence.7 ESGE recommends the use of saline instillation with a 19G needle and an electrocautery-enhanced LAMS for EUS-directed transgastric endoscopic retrograde cholangiopancreatography (EDGE) procedures.Strong recommendation, low quality evidence.8 ESGE recommends the use of either 15- or 20-mm LAMSs for EDGE, with a preference for 20-mm LAMSs when considering a same-session ERCP.Strong recommendation, low quality evidence.